Frequent callers to and users of emergency medical systems: a systematic review. Issue 8 (3rd July 2013) - Scott, Jason; Strickland, Annette Patricia; Warner, Karen; Dawson, Pamela
Abstract : Background: There appears to be a paucity of studies examining the characteristics and impact of frequent users upon emergency medical services (EMS). Objective: To review current primary research on frequent users of EMS and to identify possible gaps in the literature. Methods: Ovid, PubMed and CINAHL/Medline were systematically searched for articles that were published in English and either referred to frequent callers to or users of an EMS, or referred to frequent users of other services where admissions were via ambulance. Studies were included regardless of quality. Findings: Eighteen studies were included. Ten were emergency department based, seven in EMS and one in a psychiatric emergency service. In emergency department studies, frequent users were more likely to arrive via ambulance than infrequent users. In EMS studies, between 0.2% and 23% of patients using EMS were frequent users accounting for 1.4% to 40% of all ambulance use. No two EMS studies used the same definition of a frequent user. No studies focused on characteristics of callers to EMS. Two studies explored interventions for frequent callers to EMS, with mixed results in reducing ambulance use. Discussion: It is unknown to what extent frequent callers impact upon EMS resources. Research should identify predictors and characteristics of frequent users of EMS, and a consistent definition of a frequent caller to or user of EMS would provide greater comparability. The lack of studies identified in this review suggests that further research is needed in order to inform policy and practice.